2018
DOI: 10.1111/1911-3846.12429
|View full text |Cite
|
Sign up to set email alerts
|

The Monitoring Effectiveness of Co‐opted Audit Committees

Abstract: We investigate the relation between audit committee co‐option and financial reporting quality, where audit committee co‐option is measured as the proportion of audit committee members who joined the board after the appointment of the current Chief Executive Officer (CEO). Because CEOs are often actively involved in the director nomination and selection process, we expect that higher levels of audit committee co‐option will be associated with less effective monitoring, as evidenced by more financial statement m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 112 publications
(196 reference statements)
3
36
0
Order By: Relevance
“…To test whether CEO or CFO influence over the audit committee negates the benefits of accounting expertise on the audit committee for promoting audit quality, we form two subsamples limited to observations where CEO or CFO influence over the audit committee is above the sample median. Following Cassell et al (2018), we measure CEO influence as the proportion of audit 24. H1 Sample C includes the 462 company-year observations with an ICMW plus 111 company-year observations that do not report an ICMW but subsequently restate (using any form of restatement announcement) and disclose an ICMW or significant deficiency in internal control in the interim third quarter, for a total of 573 company-year observations.…”
Section: Ceo and Cfo Influence Over The Audit Committeementioning
confidence: 99%
See 2 more Smart Citations
“…To test whether CEO or CFO influence over the audit committee negates the benefits of accounting expertise on the audit committee for promoting audit quality, we form two subsamples limited to observations where CEO or CFO influence over the audit committee is above the sample median. Following Cassell et al (2018), we measure CEO influence as the proportion of audit 24. H1 Sample C includes the 462 company-year observations with an ICMW plus 111 company-year observations that do not report an ICMW but subsequently restate (using any form of restatement announcement) and disclose an ICMW or significant deficiency in internal control in the interim third quarter, for a total of 573 company-year observations.…”
Section: Ceo and Cfo Influence Over The Audit Committeementioning
confidence: 99%
“…To test whether CEO or CFO influence over the audit committee negates the benefits of accounting expertise on the audit committee for promoting audit quality, we form two subsamples limited to observations where CEO or CFO influence over the audit committee is above the sample median. Following Cassell et al (), we measure CEO influence as the proportion of audit committee members who joined the board subsequent to the CEO taking office, and following Beck and Mauldin () we measure CFO influence as the sample quartile ranking of CFO tenure minus the sample quartile ranking of average audit committee tenure. We then reestimate equations using these two subsamples.…”
Section: Supplemental and Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Cassell et al (2018) suggest that a co-opted audit committee chair could feel a sense of allegiance to the CEO and this could impact their monitoring of financial reporting choices.…”
Section: Audit Alumni and Executive Turnovermentioning
confidence: 99%
“…The expansion of management power makes it possible to capture "audit committee" or nurture "own people" (Xie Deren and Tang Xiaoyan, 2012). Cassell et al (2016) argue that if the audit committee is later than the current general manager, the nomination and appointment of the audit committee is likely to be intervened by the general manager, which is called the difference in service time and the percentage of time difference and financial misstatement, earnings management is positively related. Lisic et al (2013) defined the time of taking office which is earlier than the current general manager of the audit committee's as "substantive independence" and found that the "substantive independence" of the audit committee had a stronger level of independent judgment than other audit members in the course of their duties.…”
Section: Theoretical Analysismentioning
confidence: 99%